Sharing Research Data to Improve Public Health: A Funder Perspective. (July 2015) - Carr, David; Littler, Katherine
Through the Public Health Research Data Forum, global health research funders are working together to increase the availability of public health and epidemiology research data in ways that are equitable, ethical, and efficient. The Wellcome Trust funded the research reported in this special edition as a first step toward building an evidence base on the perspectives of research stakeholders in low- and middle-income countries on the benefits and challenges of sharing health research data. We hope this work will make a key contribution to discussions aimed at creating policy frameworks for data access at local, national, and regional levels that are sensitive to different contexts and ensure the benefits to research and health are realized in an equitable manner.